Research on the Goals, Principles, and Implementation Paths of Strengthening Labor Education for College Students in the New Era - Ren, Yawen (Journal of Theory and Practice of Social Science, 2024)
In the process of strengthening labor education for college students in the new era, it is necessary to clarify the relevant components of labor education. After determining the goals, principles, and paths of labor education, it can better promote university labor education to update concepts, improve cognition, and improve management mechanisms, ultimately striving to create the best atmosphere for campus labor education. In the new era of university education, by promoting the spirit of labor, we guide college students to advocate labor and recognize the importance of labor. Therefore, universities have put forward new requirements and tasks for labor education. Through labor education, we cultivate college students to establish correct labor values and provide a solid talent guarantee for achieving the great rejuvenation of the Chinese nation. With the continuous development of China's economy, venture capital has gradually developed in China since the 1990s. Venture capital can not only promote a country's economic growth, but also play an important role in increasing employment. However, due to the late start, rapid development, short time and insufficient experience of China's venture capital industry, many problems have emerged in its development, which has seriously hindered the progress of China's venture capital industry. This paper summarizes and analyzes the problems in the development of venture capital industry, draws on the successful experience of some western developed countries in venture capital, and puts forward corresponding solutions. In order to promote the development and improvement of China's venture capital industry and enhance the competitiveness of venture capital companies.